2021
DOI: 10.2147/ijn.s315782
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Pharmacokinetic Evaluation of Synergistic Fenbendazole and Rapamycin Co-Encapsulated in Methoxy Poly(Ethylene Glycol)-b-Poly(Caprolactone) Polymeric Micelles

Abstract: We aimed to develop a nanocarrier formulation incorporating fenbendazole (FEN) and rapamycin (RAPA) with strong efficacy against A549 cancer cells. As FEN and RAPA are poorly soluble in water, it is difficult to apply them clinically in vivo. Therefore, we attempted to resolve this problem by encapsulating these drugs in polymeric micelles. Methods: We evaluated drug synergy using the combination index (CI) values of various molar ratios of FEN and RAPA. We formed and tested micelles composed of different po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…The comparison of one- and two-compartment kinetic models indicated that the two-compartment model with first-order elimination from the central compartment described rapamycin blood concentration time profiles better than the one-compartment model. The observed kinetic behavior of rapamycin is consistent with that documented in preclinical and clinical pharmacokinetic studies [ 44 , 45 , 46 ]. The results of the disposition kinetics characterization following a single IV dose of 0.1 mg/kg unformulated free rapamycin or rapamycin nanoparticles in C57BL/6 mice demonstrated that the blood concentration time profile of rapamycin follows a biexponential time course typical of two-compartment disposition.…”
Section: Discussionsupporting
confidence: 86%
“…The comparison of one- and two-compartment kinetic models indicated that the two-compartment model with first-order elimination from the central compartment described rapamycin blood concentration time profiles better than the one-compartment model. The observed kinetic behavior of rapamycin is consistent with that documented in preclinical and clinical pharmacokinetic studies [ 44 , 45 , 46 ]. The results of the disposition kinetics characterization following a single IV dose of 0.1 mg/kg unformulated free rapamycin or rapamycin nanoparticles in C57BL/6 mice demonstrated that the blood concentration time profile of rapamycin follows a biexponential time course typical of two-compartment disposition.…”
Section: Discussionsupporting
confidence: 86%
“…Although surgical and chemotherapy strategies for treating OC are evolving [63], the 5-year overall survival rate for OC remains low at 40%. The development of novel treatments for OC is, therefore, needed; micelles, used in combination therapy, may be an alternative [64,65]. The advantage of combination therapy is that anticancer drugs with different mechanisms can be applied to OC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For micelles, it can be hypothesized that the PTX/SRF from micelles was released at a slower rate than the free drug. This is because it was absorbed into cancer cells, increasing the CI value [65,71]. In the in vitro cytotoxicity evaluation, the free drug had a lower IC 50 value than did the micelle formulation as it is applied directly to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Drug combination therapy using several different mechanisms has emerged as a way to improve the limitations of multidrug resistance and side effects associated with high doses of single dosage forms [ 8 , 9 ]. Such combination therapy has been regarded as a promising therapeutic strategy as it reduces anticancer drug resistance, overcomes tumor heterogeneity, and provides synergistic anticancer effects [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%